United Kingdom : Financial Sector Assessment Program-Systemic Risk and Interconnectedness Analysis-Technical Note. (IMF Staff Country Reports; Country Report, 2016)
This paper summarizes the assessment of interconnectedness and systemic risk undertaken for the U.K. financial system as part of the Financial Sector Assessment Program. It consists of three parts, focusing on the following: (1) motivation for monitoring cross-sector interconnectedness as part of the financial system's resilience assessment, (2) description of selected empirical methods that may be employed to analyze interconnectedness, and (3) an illustrative analysis conducted, based on a definition of the financial system that incorporates U.K. banking and life insurance sectors. The assessment of financial system resilience should account for the evolution of interconnectedness between firms and sectors.